2022
DOI: 10.1002/rth2.12779
|View full text |Cite
|
Sign up to set email alerts
|

Impact of deep vein thrombosis on adolescent athletes: Navigating an invisible disability

Abstract: Background Injury in adolescent athletes that threatens their sport participation can result in a sense of identity loss during critical years for identity development, creating the potential for significant mental health challenges. The specific effect of deep vein thrombosis (DVT) in this vulnerable population has not been characterized. Purpose To describe the impact of DVT diagnosis, treatment, and long‐term complications on the mental well‐being of athletes who sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Moreover, a recent study from Bastas et al. [ 17 ] found that adolescent athletes who are diagnosed with deep vein thrombosis (DVT) have a significant need for a variety of support services, indicating the potential importance of this construct for VTE survivors in a return to activity.…”
Section: Introductionmentioning
confidence: 99%